The Method of Markov Processes with Macro States for Analysis of Unreliable Telecommunication Systems - Rindzevicius, R.; Tervydis, P.; Daunys, A. (Elektronika ir Elektrotechnika, 2012)
Our proposed analysis method of macro state Markov model has the advantages over detailed state Markov model. The data packet loss in telecommunication system with the unreliable data packet transmission links is modeled as a continuous time and the discrete states Markov process. The advantages of the macro state Markov model method were demonstrated by modeling two channels unreliable telecommunication system with losses and providing some numerical illustrations. The application of the proposed method for analysis of an unreliable data packet transmission system and queueing system is discussed. All investigated systems are presented according Kendall’s notation. On the basis of the reached outcomes it is possible to say that there are negligible differences between the results of macro and detailed states Markov models for the wide value parameters of investigated unreliable loss system M/M/2/2. Ill. 7, bibl. 10 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.118.2.1177